Intruder familiarity and not duet similarity influences the territory defense in a year-round territorial bird species - Hamzaj, Tihana (2022)
To avoid unnecessary energy expenditures in territorial defense, many species (e.g., insects, amphibians, birds, and mammals) have developed the capability to distinguish between different intruder types using visual, acoustic, and/or chemical signals. Determining the mechanism used for intruder recognition is key to understanding the dynamics of territorial behaviors. In birds that use vocalizations for territorial defense, the frequency and duration of vocalizations or the familiarity with the intruder may be the main mechanism used for intruder recognition. Here, we conducted a playback experiment with territorial White-eared Ground-sparrows (Melozone leucotis), to analyze if territorial pairs recognize intruders using frequency and duration characteristics (a bird's response is based on how structurally similar the intruders' duets are to their own) or by familiarity with the intruders (neighbors vs. non-neighbors). We focused on duets because this species uses duets exclusively for territorial defense. We broadcasted a duet from a territorial neighbor, two duets from non-neighbors (with different frequency and duration characteristics), and a duet from a control species in 39 territorial pair from three populations. During playback we measured five behavioral responses: latency of the first vocalization, latency of the approach to the speaker, time spent close the speaker (within 5 m), number of individuals that approached the speaker, and the number of vocalizations. We found that territorial White-eared Ground-sparrow pairs responded stronger to neighbors than non-neighbors, and this response is not influenced by duet duration or frequency characteristics. This result suggests that neighbors represent a greater territorial threat for White-eared Ground-sparrows than non-neighbors. Further work is necessary to understand how common this observation is for tropical species that defend small territories year-round.